2017
DOI: 10.1101/110197
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The mutation rates and mutational bias of influenza A virus

Abstract: Word Count: 250Main Text Word Count: 6,762 peer-reviewed) is the author/funder. All rights reserved. No reuse allowed without permission.The copyright holder for this preprint (which was not . http://dx.doi.org/10.1101/110197 doi: bioRxiv preprint first posted online Feb. 21, 2017; 1 Abstract 1

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…The use of the minigenome assay allowed us to see all mutations generated by polymerase and not just those that would allow viable viruses. Pauly et al have recently shown that the mutation rate for influenza has been significantly underestimated by only counting mutations which occur in plaque forming viruses 47 . Sequencing only viruses which have exited the cell ignores mutations that cause defects in packaging or cellular exit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of the minigenome assay allowed us to see all mutations generated by polymerase and not just those that would allow viable viruses. Pauly et al have recently shown that the mutation rate for influenza has been significantly underestimated by only counting mutations which occur in plaque forming viruses 47 . Sequencing only viruses which have exited the cell ignores mutations that cause defects in packaging or cellular exit.…”
Section: Discussionmentioning
confidence: 99%
“…Although Primer ID can remove sequencing error, it is still impossible to distinguish between errors due to the flu polymerase and the reverse transcriptase used during the Primer ID reaction. A recent paper has suggested that care must be taken as these two error rates are the same order of magnitude 47 . For this reason, we have not reported an absolute error rate but a relative error rate compared to the drug-free baseline sample.…”
Section: Discussionmentioning
confidence: 99%
“…Further experiments should explore the mutational landscape of PpyrOMLV1 & 2, which appears to be significantly lower than of Influenzaviruses, specifically Influenza A virus, which are characterized by high mutational rate (ca. 1 mutation per genome replication) associated to the absence of RNA proofreading enzymes (271). In addition we evaluated the presence of PpyrOMLV1 & 2 on diverse tissues and organs of P. pyralis.…”
Section: Photinus Pyralis Orthomyxo-like Virusesmentioning
confidence: 99%
“…The most commonly identified mechanism of mutagen resistance in RNA viruses is altered baseline polymerase fidelity. We determined the baseline mutation rate of our three 5FU resistant variants using a Luria-Delbrück fluctuation test that can measure the rates of all 12 mutational classes ((11) and Figure 3). We also evaluated PB1 V43I, which has been reported to be a fidelity variant (20, 43).…”
Section: Resultsmentioning
confidence: 99%
“…As in many RNA viruses, influenza virus’ low fidelity is due to the absence of proofreading and repair mechanisms during genome replication (8-10). We have previously estimated influenza’s mutation rate to be greater than 1 × 10 −4 mutations per nucleotide per RNA strand replicated, which suggests that approximately 2 new mutations are introduced into every newly synthesized genome (11). As a result, influenza viruses exist as swarms of distinct genetic variants, which provide a rich substrate for natural selection of adaptive mutations.…”
Section: Introductionmentioning
confidence: 99%